ANALYSIS OF ADOLESCENT REPRODUCTIVE HEALTH EDUCATION PROGRAMS AT SENIOR HIGH SCHOOLS LEVEL IN OGAN ILIR REGENCY - Oktaria, Risma; Martha, Evi (HEARTY, 2025)
All adolescents are entitled to access reproductive health services that are appropriate to their developmental stage, both through formal and non-formal education. Preliminary findings indicate that students generally lack adequate knowledge of reproductive health, with limited information provided both at school and within the family. Teachers report that students tend to feel embarrassed or consider discussions on marriage and reproductive health to be taboo. This study aims to analyze the implementation of adolescent reproductive health education programs at the senior high school level in Ogan Ilir Regency, Indonesia. This qualitative study employed in-depth interviews with teachers, community health center personnel, and family planning counselors, along with two key informants, four student focus group discussions (FGDs) and document analysis. The findings reveal that all schools have made efforts to implement adolescent reproductive health education through teacher-led instruction, the Youth Care Health Services (Pelayanan Kesehatan Peduli Remaja/PKPR) program, and the Youth Information and Counseling Center (Pusat Informasi dan Konseling Remaja/PIK-R) initiative. However, personnel involved in these programs require further training to enhance their knowledge and competencies. While implementation guidelines are available, several adjustments are often made during practice. Key challenges identified include limited budget allocations, insufficient facilities and resources, and restricted accessibility for some adolescents. Although reproductive health education through teacher instruction, PKPR, and PIK-R programs provides significant benefits for adolescents, further efforts are needed to optimize their implementation and outreach.